Antioxidant Activity and Inhibition of Α-Glucosidase from Yellow Root Extract (Fatuoa Pilosa Gaudich) In Vitro - Tukan, Maria Magdalena Nona Motu; Falah, Samsul; Andrianto, Dimas; Najmah, Najmah (Jambura Journal of Chemistry, 2023)
Yellow root (Fatoua pilosa Gaudich) is a type of plant which is found on lowland mostly in Japan, China and usually grow in the dry bushes. Traditionally, the yellow root (Fatuoa pilosa Gaudich) is used to treat the disease of diabetes mellitus and as antiinflamation. One of the causes of diabetes disease is oxidative stress. Oxidative stress can be reduced by using antioxidants. This research aims to explore antioxidant activity and inhibition of α-glucosidase enzyme from yellow root extract (Fatoua pilosa Gaudich.). Quantitative determination of total phenolic by using folin-ciocalteu method declared as gallic acid equivalents (GAE) per gram of extract, levels of total flavonoids with AlCl3 method declared as Quercetin equivalen (QE), and antioxidant activity in fertilization with the DPPH (2, 2-diphenyl-1- picrylhydrazyl) stated in the IC50 (concentration inhibition). The Results showed that the highest levels of total flavonoids was in extract ethanol 96% 199.44 g QE/g extract, while the total phenolic levels highest in 70% ethanol extracts 211.54 mg GAE/g extract. The highest IC50 obtained from antioxidant test of yellow root extrat was 70% ethanol extract 14.62 μg/mL and the most active fraction that can inhibit α-glucosidase enzyme was of ethyl acetate fraction with IC50 values 680.54 μg/mL.